The association between playing video games and thumb/wrist pain among medical students - Altuwairqi, Abdullah (Journal of King Abdulaziz University: Medical Sciences, 2024)
De Quervain’s disease is characterized by stennosing tenosynovitis in the first extensor wrist compartment. With the growing popularity of video gaming, the incidence of de Quervain’s disease has continued to rise among teenagers and youths. There is a need to determine the correlation between gaming and de Quervain’s disease. To assess the association between playing video games and thumb and wrist pain among medical students in the King Abdulaziz University. This cross-sectional survey study was conducted among medical students at the King Abdulaziz University between July 2020 and October 2020. Statistical analyses were performed using SPSS version 23. Most medical students (82%) played video games; among them, 36% and 59% reported using PlayStations and mobile phones, respectively. The mean ± SD pain severity was 1.63 ± 2.65, with 1.4% and 62.9% reported experiencing the most severe pain and no pain, respectively. Further, 12.9%, 15.1%, and 10.1% of the participants reported stretching their fingers before playing, having problems carrying things, and the pain affecting their daily activities, respectively. Most of our participants played video games mainly using mobile phones and PlayStations. However, a majority of them did not experience any pain; moreover, we observed an association of pain episodes and severity with the playing duration and devices used